Contending Conceptions of Competition and the Role of Regulating Capital - Tsoulfidis, Lefteris (Panoeconomicus, 2015)
This article discusses two major conceptions of competition, the classical and the neoclassical. In the classical conception, competition is viewed as a dynamic rivalrous process of firms struggling with one another over the expansion of their market shares at the expense of their competitors. This dynamic view of competition characterizes mainly the works of Smith, Ricardo, J. S. Mill and Marx; a similar view can be also found in the writings of Austrian economists and the business literature. By contrast, the neoclassical conception of competition is derived from the requirements of a theory geared towards static equilibrium and not from any historical observation of the way in which firms actually organize and compete with one another. Key words: Classical competition, Marxian competition, Regulating capital, Incremental rate of return, Flatness profit ratio. JEL: B12, B13, B14, L11.